2019
DOI: 10.5194/essd-11-1083-2019
|View full text |Cite
|
Sign up to set email alerts
|

New 30 m resolution Hong Kong climate, vegetation, and topography rasters indicate greater spatial variation than global grids within an urban mosaic

Abstract: Abstract. The recent proliferation of high-quality global gridded environmental datasets has spurred a renaissance of studies in many fields, including biogeography. However, these data, often 1 km at the finest scale available, are too coarse for applications such as precise designation of conservation priority areas and regional species distribution modeling, or purposes outside of biology such as city planning and precision agriculture. Further, these global datasets likely underestimate local climate varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Unfortunately, available datasets do not allow explicit consideration of the urban anomaly of air temperature and temperature-dependent malaria indicators in the MaxEnt model. The network of weather stations in Moscow region is too sparse for such a task, while globally available gridded temperature datasets are unable to adequately represent temperature heterogeneity in urban areas [46]. Development of detailed and reliable climatic datasets is essential for better understanding of epidemiological threats in urban areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, available datasets do not allow explicit consideration of the urban anomaly of air temperature and temperature-dependent malaria indicators in the MaxEnt model. The network of weather stations in Moscow region is too sparse for such a task, while globally available gridded temperature datasets are unable to adequately represent temperature heterogeneity in urban areas [46]. Development of detailed and reliable climatic datasets is essential for better understanding of epidemiological threats in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…A popular WorldClim gridded data set with 1-km spatial resolution were used [38] as a source of climatic information for geospatial analysis. It is emphasized that despite high spatial resolution, the WorldClim data on air temperature is not perfect, especially for urban areas, where significant underestimation of temperature spatial variability was revealed [46]. WorldClim data reasonably resolves the elevation-induced local climate features, e.g., lower daytime temperatures in the lowlands, however the representation of Moscow UHI was found to be unsatisfactory.…”
Section: Climate and Environmental Datamentioning
confidence: 96%
“…At each plot, we also estimated the percentage of ground cover (Ground Cover) by applying colour thresholding techniques in ImageJ (Abramoff, 2004) to digital photographs, and obtained high resolution (30 x 30 m) estimates of mean annual temperature (Temperature) from local climate models (developed by Morgan & Guénard, 2019). As these environmental factors were shown to influence ant diversity in other invaded systems (e.g.…”
Section: Sampling Ant Assemblages and Environmental Variablesmentioning
confidence: 99%
“…To quantify landscape connectivity of each sampling site, we measured vegetation density within 500 m radius buffer using a 30 m NDVI raster (Morgan and Guénard 2019). We set buffer radius at 500 m, as Tsang and Bonebrake (2017) showed that this scale performed better than others in shaping butterfly composition in Hong Kong urban parks.…”
Section: Environmental Variablesmentioning
confidence: 99%